THE DEVELOPMENT OF NATIONAL FOOD ESTATE: THE INDONESIAN FOOD CRISIS ANTICIPATION STRATEGY - Lasminingrat, Lula; Efriza, Efriza (Jurnal Pertahanan dan Bela Negara, 2020)
Indonesia responds to the urgency of the threat of food crisis by developing national food estate. According to reports released by FAO and United Nations, the Covid-19 pandemic has the potential to threaten more than 50 million people towards extreme poverty. This has an impact on the global food crisis that threatens other countries if they do not take the right steps immediately. Food crisis is one of the non-traditional threats because it has significant impact on lives of many people in a country. Non-traditional threats are defined as security threats that hit a country non-militarily, it can be in the form of issues of climate change, economy, limited resources, disease outbreaks, or food security. Food security can be achieved when access to food can be easily achieved by all elements of society and meets the domestic needs. However, when access to food cannot be easily accessed by public, it creates a potential for a food crisis. This is because food is the primary need of every individual which must be fulfilled at any time so it is a national security issue. Through these problems, the availability of national food security must be guaranteed by the government. Along with high population growth and a pandemic outbreak, national food security and stability is on the verge of limitations. This article aims to explain the development of food estate as Indonesia’s strategy in facing the threat of food crisis in the next few years. This research used qualitative analysis method to understand the urgency of the development of food estate as a way for Indonesia to face the threat of food crisis by using the theory of threats, food security, and food estate. In this case, Jokowi responded to the threat of the food crisis by building national food estate in Central Kalimantan. The development of national food estate is considered to be able to meet Indonesia’s food reserves in the next few years, especially after the pandemic period. The results of the research in this article show that the government sees the potential for the food crisis as a national threat, so it needs measurable steps that can overcome these problems and pay attention to the sustainability aspect in its implementation. Therefore, building a food estate is the right step to answer this challenge. Keywords: non-traditional threat, food crises, food security, food estate, national security